Nature’s Power and Native Persistence: The Influence of First Nations and the Environment is the Development of the Mattagami Hydro-Electric System During the Twentieth Century - Manore, Jean (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractTo date, most analyses of hydro-electric development portray the environment and Aboriginal Peoples as victims unable to alter or resist its intrusion on to the landscape. However, an examination of the Mattagami river developments in northeastern Ontario illustrates that environmental conditions constantly influence the shape and development of the hydro-electric system. Also, while the ability of the northeastern Aboriginal Peoples to affect hydro-electric development is limited for much of this century, by the 1990s, their persistence and perseverance coalesces with changing court decisions and legislation, empowering them to negotiate with Ontario Hydro a moratorium on further development on the Mattagami River.